Performance assessment of medical service for organ transplant department based on diagnosis-related groups: A programme incorporating ischemia-free liver transplantation in China - Lu, Jianjun; Lin, Zhuochen; Xiong, Ying; Pang, Hui; Zhang, Ye; Xin, Ziyi; Li, Yuelin; Shen, Zhiqing; Chen, Wei; Zhang, Wujun (Frontiers in Public Health, 2023)
Background: In July 2017, the first affiliated hospital of Sun Yat-sen university carried out the world's first case of ischemia-free liver transplantation (IFLT). This study aimed to evaluate the performance of medical services pre- and post-IFLT implementation in the organ transplant department of this hospital based on diagnosis-related groups, so as to provide a data basis for the clinical practice of the organ transplant specialty. Methods: The first pages of medical records of inpatients in the organ transplant department from 2016 to 2019 were collected. The China version Diagnosis-related groups (DRGs) were used as a risk adjustment tool to compare the income structure, service availability, service efficiency and service safety of the organ transplant department between the pre- and post-IFLT implementation periods. Results: Income structure of the organ transplant department was more optimized in the post-IFLT period compared with that in the pre-IFLT period. Medical service performance parameters of the organ transplant department in the post-IFLT period were better than those in the pre-IFLT period. Specifically, case mix index values were 2.65 and 2.89 in the pre- and post-IFLT periods, respectively (P = 0.173). Proportions of organ transplantation cases were 14.16% and 18.27%, respectively (P < 0.001). Compared with that in the pre-IFLT period, the average postoperative hospital stay of liver transplants decreased by 11.40% (30.17 vs. 26.73 days, P = 0.006), and the average postoperative hospital stay of renal transplants decreased by 7.61% (25.23 vs.23.31 days, P = 0.092). Cost efficiency index decreased significantly compared with that in the pre-IFLT period (P < 0.001), while time efficiency index fluctuated around 0.83 in the pre- and post-IFLT periods (P = 0.725). Moreover, the average postoperative hospital stay of IFLT cases was significantly shorter than that of conventional liver transplant cases (P = 0.001). Conclusion: The application of IFLT technology could contribute to improving the medical service performance of the organ transplant department. Meanwhile, the DRGs tool may help transplant departments to coordinate the future delivery planning of medical service.